Analisa Communication Gap Antara Harapan dan Layanan Aktual Dalam Layanan Telkom Speedy di Kota Ambon - Marthen B. A. Risakotta; A. L. Kakerissa (Industrial Engineering Study Program, Pattimura University, 2015)
PT. Telekomunikasi Indonesia Tbk., a state-owned enterprise and the largest service and network provider in Indonesia, always prioritizes to meet the need of consumers. The fit between consumers want and company's services become one measure of the success of the company's performance. Therefore, a research is conducted to study a communication gap of Telkom Speedy Services, which is measured by a comparison of customer expectation yielding by promotion activities and customer perception forming by actual services. Result shows a significant difference between customer expectation and customer perception.